FAKTOR –FAKTOR YANG MEMPENGARUHI KUALITAS AIR MINUM PADA DEPOT AIR MINUM DI KOTA BENGKULU TAHUN 2012 - Jubaidi, Jubaidi (Politeknik Kesehatan Kemenkes Bengkulu, 2012)
Drinking water quality is one of the basic needs of society. In fulfilling its needs, the community has sought a way to buy a gallon of drinking water refill at a cheap price. The purpose of this study was to determine the factors that affect drinking water quality in drinking water depots in the city of Bengkulu. This study is a survey research with cross sectional approach, a sample size in this study as many as 163 samples. Primary data processed by the regression test followed by logistic regression test.The results showed that the dominant factor is the effect of drinking water treatment process with a value of p = 0.000 and Exp. B = 4.454.Recommended for drinking water depots entrepreneurs in drinking water treatment processes to use micro filters with a diameter smaller than viruses, provide training for employees or managers of drinking water and perform maintenance of drinking water processing components on time and as well as the guidance and supervision on a regular basis by the government.